Latent microbial reactivation and immune dysregulation in sarcoidosis: bridging pathogenesis and precision therapeutics - Sawahata, Michiru; Uchida, Keisuke; Furukawa, Asuka; Eishi, Yoshinobu; Maemondo, Makoto (Frontiers in Medicine, 2025)
Sarcoidosis, a systemic granulomatous disease of unknown etiology, is characterized by the formation of non-caseating granulomas affecting multiple organs. Accumulating evidence implicates Cutibacterium acnes (C. acnes; formerly Propionibacterium acnes) as a potential microbial trigger. The consistent detection of C. acnes within sarcoid granulomas, along with associated Th1-polarized immune responses, indicates that latent intracellular persistence and reactivation of this commensal bacterium may drive granulomatous inflammation. This bacterium can persist intracellularly within macrophages and dendritic cells and, upon reactivation, may induce Th1/Th17-dominant immune responses in genetically and immunologically susceptible individuals. Immune dysregulation, including deficient C. acnes-specific regulatory T cell (Treg) responses, may underlie the unchecked effector activity that sustains inflammation. Enhanced C. acnes-specific T-cell reactivity, including elevated interferon-γ and interleukin-2 production, is observed in some patients, supporting this hypothesis. Although direct evidence for C. acnes-specific Tregs and antigen-specific T-cell responses is limited, immune dysregulation involving impaired tolerance is thought to contribute to the heterogeneity of sarcoidosis, which ranges from spontaneous remission to chronic fibrotic progression. Recent advances in diagnostic tools, including P. acnes-specific monoclonal antibody immunostaining and T-cell assays specific to C. acnes, offer promising approaches for detecting microbial involvement. These developments highlight the importance of etiology-driven treatment strategies. As sarcoidosis likely comprises a spectrum of underlying causes, etiology-specific interventions are particularly warranted upon the identification of a defined trigger, such as C. acnes. This review explores the potential pathogenesis of sarcoidosis, focusing on latent microbial reactivation, immune dysregulation, and their diagnostic and therapeutic implications, and highlights opportunities for precision medicine.